Efektivitas Penggunaan Media Tanam Berbasis Agen Bioteknologi Terhadap Pertumbuhan Tanaman Hias Episcia cupreata - Isnin Meiva; Ida Yayu Nurul Hizqiyah; Cartono (Biotropic : The Journal of Tropical Biology, 2022)
Planting media is the most important aspect for plant growth. However, in fact, agricultural land in Indonesia is of relatively low quality. These factors include nutrient deficits, decreased levels of organic matter, pollution, decreased microbial activity, and salinization/alkalinization. This study aims to determine the effectiveness of the use of planting media based on biotechnology agents on the growth of Episcia cupreata. The method is a quasi-experimental, RAK design (Randomized Block Design) with 6 treatments, 4 treatments. Main data analysis with ANOVA test and DMRT test level 5% and supporting data with correlation analysis. The result shows the effectiveness of using planting media based on biotechnology agents on the growth of Episcia cupreata. The most optimal growth of the number of leaves produced by treatment T1 with an average of 19.75, stem height by treatment T2 with an average of 48 cm, and root length by treatment T2 with an average of 10,27 cm. Physicochemical conditions include soil pH, temperature, air humidity, soil moisture, and light intensity were correlated with the growth of Episcia cupreata.